Who did safety nets catch during the Great Recession and how? A comparison of eleven OECD countries - Katherine Baird (Luxembourg Income Study (LIS), 2014)
How adequately did governments protect their citizens over the Great Recession? The recent recession, the worst since the Great Depression, provides an opportune moment to investigate the adequacy and fairness of countries' responses to an economic crisis. Using household-level LIS data from eleven OECD nations, I calculate the recession's impact among the non-elderly population on earned income across the income distribution, and investigate the degree to which additional government transfers compensated for these losses. While the recession's impact on earned income varied significantly both across and within countries, in most countries additional government transfers to citizens offset the steep declines in household incomes that occurred along the income distribution, and reversed increases in inequality. A notable shortcoming across many countries was that the protection provided to income shocks was not progressively distributed; in a number of countries, the lowest income citizens experienced the sharpest drops in disposable income. Investigating patterns of responses across the different countries fails to verify "path dependency" claims about how welfare state regimes differ, and how their responses to income shocks might vary; instead I find support for predictions of a convergence in welfare state policy.
Keywords: 330; Great Recession; Income Redistribution; Inequality; Comparative Social Policy; Luxembourg Income Study